Innovative sources for development finance: over-arching issues - A.B. Atkinson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
In analysing proposals for new sources of development funding, there are several issues that arise across the board. What is the role of new sources in relation to existing overseas development assistance? Should we be seeking new sources that generate a double dividend? Can the key elements of a proposal be achieved by another route? What should be the fiscal architecture? Is there a modern transfer problem? It is with these general concerns that the present paper deals. Its aim is to bring to bear on global public finance the accumulated knowledge in the field of national public finance, and more generally public economics.
Keywords: O2; 330; development finance; international public finance; double dividend; fiscal architecture; development assistance; Entwicklungshilfe; Entwicklungsfinanzierung